Integrating consumer perspectives into a large-scale health literacy audit of health information materials: learnings and next steps - Julie Ayre; Carissa Bonner; Jemma Gonzalez; Teresa Vaccaro; Michael Cousins; Kirsten McCaffery; Danielle M. Muscat (BMC, 2023)
Abstract Background Health information is less effective when it does not meet the health literacy needs of its consumers. For health organisations, assessing the appropriateness of their existing health information resources is a key step to addressing this issue. This study describes novel methods for a consumer-centred large-scale health literacy audit of existing resources and reflects on opportunities to further refine the method. Methods This audit focused on resources developed by NPS MedicineWise, an Australian not-for-profit that promotes safe and informed use of medicines. The audit comprised 4 stages, with consumers engaged at each stage: 1) Select a sample of resources for assessment; 2) Assess the sample using subjective (Patient Education Materials Assessment Tool) and objective (Sydney Health Literacy Lab Health Literacy Editor) assessment tools; 3) Review audit findings through workshops and identify priority areas for future work; 4) Reflect and gather feedback on the audit process via interviews. Results Of 147 resources, consumers selected 49 for detailed assessment that covered a range of health topics, health literacy skills, and formats, and which had varied web usage. Overall, 42 resources (85.7%) were assessed as easy to understand, but only 26 (53.1%) as easy to act on. A typical text was written at a grade 12 reading level and used the passive voice 6 times. About one in five words in a typical text were considered complex (19%). Workshops identified three key areas for action: make resources easier to understand and act on; consider the readers' context, needs, and skills; and improve inclusiveness and representation. Interviews with workshop attendees highlighted that audit methods could be further improved by setting clear expectations about the project rationale, objectives, and consumer roles; providing consumers with a simpler subjective health literacy assessment tool, and addressing issues related to diverse representation. Conclusions This audit yielded valuable consumer-centred priorities for improving organisational health literacy with regards to updating a large existing database of health information resources. We also identified important opportunities to further refine the process. Study findings provide valuable practical insights that can inform organisational health actions for the upcoming Australian National Health Literacy Strategy.